PENGGUNAAN MEDIA AL-QUR’AN BRAILLE BOOK DAN BRAILLE DIGITAL BAGI TUNANETRA DI SURAKARTA - Widiarti, Faridatul Husna (Profetika Jurnal Studi Islam, 2018)
Qur'anic learning is needed by all Muslims. The learning process starts from studying the Qur'an, reading the verses of the Qur'an, understanding the contents and content of the verses of the Qur'an, practicing the content of the verses. Learning requires media or an effective intermediary. The learning of the Qur'an uses the Qur'an's media. Particularly for blind disability students, students who experience obstacles in their vision either do not function one or do not function both, the Qur'anic learning requires media that are in accordance with the abilities of students. The media used in the Al-Qur'an learning for net disabilities is the Al-Qur'an Braille. The researcher conducted a study of community organizations in the city of Surakarta, the organization of the Indonesian Muslim Blind Association in the Surakarta Regional Leadership Council in 2018 which organizes Qur'anic learning with the media of the Qur’an Braille book and the digital Braille Qur'an. Problems begin with (1) How can the use of the Koran Braille book and al-Qur'an digital Braille (2) what are the advantages and disadvantages of using digital Braille book and al-Qur'an Braille media ( 3) how successful is the use of the Braille book and digital Braille al-Qur'an media. Aim to find out the uses, strengths and weaknesses, and the level of success of the Koran Braille book and the digital Braille Qur'an. This study uses qualitative descriptive data collection through field observations, interviews with a number of resource persons, documentation of events in the field. The results of this study are expected for educators to master the media used in learning, as well as for educators and observers of education to develop and innovate the learning process for blind disability learners. Pembelajaran al-Qur’an diperlukan seluruh umat muslim. Proses pembelajaran bermula dari mempelajari al-Qur’an, membaca ayat-ayat al-Qur’an, memahami isi dan kandungan ayat-ayat al-Qur’an, mengamalkan kandungan ayat-ayat tersebut. Pembelajaran memerlukan media atau perantara yang tepat guna. Pembelajaran al-Qur’an menggunakan media al-Qur’an. Khusus peserta didik disabilitas netra, peserta didik yang mengalami hambatan dalam penglihatannya baik tidak berfungsi salah satu atau tidak berfungsi keduanya, pembelajaran al-Qur’an memerlukan media yang sesuai dengan kemampuan peserta didik. Media yang digunakan pada pembelajaran al-Qur’an bagi disabilitas netra adalah al-Qur’an Braille. Peneliti melakukan penelitian terhadap organisasi masyarakat di kota Surakarta, organisasi Ikatan Tunanetra Muslim Indonesia Dewan Pimpinan Daerah Surakarta Tahun 2018 yang menyelenggarakan pembelajaran al-Qur’an dengan media al-Qur’an Braille book dan al-Qur’an Braille digital. Permasalahan berawal dari (1) Bagaimana penggunaan media al-Qur’an Braille book dan al-Qur’an Braille digital (2) Apa kelebihan dan kekurangan dari penggunaan media al-Qur’an Braille book dan al-Qur’an Braille digital (3) Bagaimana tingkat keberhasilan dari penggunaan media al-Qur’an Braille book dan al-Qur’an Braille digital. Bertujuan untuk mengetahui penggunaan, kelebihan dan kekurangan, dan tingkat keberhasilan dari media al-Qur’an Braille book dan al-Qur’an Braille digital. Penelitian ini menggunakan diskriptif kualitatif dengan pengumpulan data melalui observasi lapangan, wawancara dengan sejumlah nara sumber, dokumentasi kejadian di lapangan. Hasil dari penelitian ini diharapkan untuk pendidik menguasai media-media yang digunakan dalam pembelajaran, serta untuk pendidik dan pemerhati pendidikan untuk mengembangkan dan menginovasi proses pembelajaran bagi peserta didik disabilitas netra.